The Silent Nature in the Book Nasim al-Saba by Ibn Habib al-Halabi: A Cosmological Perspective - العجلان, طارق كطيفة اغجيري (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study explores the cosmic components and rhetorical imagery within Naseem al-Saba by Ibn Habib al-Halabi, with a focus on “still life” or non-human natural elements in literary discourse—such as water, air, celestial bodies, plants, and animals. The research aims to reveal the aesthetic and symbolic functions these cosmic elements serve in shaping the text's meaning and poetic vision. Employing a rhetorical-analytical approach, the study uncovers how such imagery operates within the linguistic and artistic structure of the text, contributing to its spiritual and contemplative dimensions. Ultimately, the study argues that the still life in Naseem al-Saba is not merely decorative, but plays a vital role in generating meaning and emotional resonance.